PENGARUH PENAMBAHAN TEPUNG JANGKRIK KALUNG (Gryllus bimaculatus) DALAM PAKAN MENCIT (Musmusculus) JANTAN TERHADAP BERAT TESTIS, DIAMETER TUBULUS SEMINIFERUS DAN JUMLAH SEL LEYDIG - SAFITRA DINDA PRAMITHA, 061411133040 (2018)
This research’s purpose is to see the effect of ‘Kalung’ cricket’s (Gryllus bimaculatus) flouraddition in male mice (Mus musculus) feed toward the testes’ weight, seminiferous tubules’ diameter, and leydig cells’ amount. The effect of cricket flour was tested on 20 mice which are randomly mixed at 4 treatments. K (control) was given standard feed, P1 was given standard feed with addition of 5% cricket flour, P2 with addition of 10% cricket flour, and P3 with addition of 20% cricket flour. Treatment was done for 45 days, then the mice were sacrificed. Testes sample was taken by surgery, testes’ weight were weighed using 0.1 analytical scale, then proceed with the preparation of histologic preparations of the seminiferous tubules to see the seminiferous tubules’ diameter and leydig cells’ amount. Measurement of seminiferous tubules’ diameter using Trinocular microscope with 100x magnification with NIS-Element High Contain Analysis software. Calculation of leydig cells’ amount using Optilab with Image Raster software with 400x magnification. The results were analyzed using Analysis of Variant (ANOVA) and continued with Duncan range test of obtian average value and standard deviation. The weight of testes are 0.09±0.016 (K), 0.13±0.015 (P1), 0.10±0.031 (P2), 0.05±0.023 (P3). Seminiferous tubules’ diameter are 174.32±8.032 (K), 204.27±18.004 (P1), 182,68 ±10.233 (P2), 139.03±13.042 (P3). Leydig cells’ amount are 11.78±2.072 (K), 16.40±2.821 (P1), 11.82±1.428 (P2), 8.26±1.342 (P3) which shows significant differences (P<0.05). Conclusion is, the addition of 5% cricket’s flour dose is the optimal dose to increase the testes’ weight, seminiferous tubules’ diameter, and leydig cells’ amount.